ANALYSIS OF HUMAN DEVELOPMENT INDEX, UNEMPLOYMENT AND POVERTY ON ECONOMIC GROWTH IN INDONESIA - Rizky Amanda Yusnuri; Jariah Abubakar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of this study is to see and analyze how much influence the Human Development index, Unemployment and Poverty on Economic Growth in Indonesia. The data used in this study is secondary data obtained from related agencies over a period of 16 years (2006 - 2021). To achieve the results of this study, multiple linear regression analysis was used using the EViews 10 program. The results of this study simultaneously showed that the Human Development Index variable had no effect on Economic Growth, then the Unemployment variable had a negative and significant effect on Economic Growth, and the Poverty variable positive and significant effect on economic growth. Simultaneously, the Human Development Index, Unemployment and Poverty variables have significant and significant impact on economic growth.